Effects of V on the dual-phase heterostructure FeCrNiVx medium-entropy alloys - Peng Sang; Ningning Liang; Lei Gu; Liangyu Chen; Yuan Lei; Zan Zhang; Yongsheng Li (Journal of Materials Research and Technology)
Multi-phase combined morphology improves the performance of medium-entropy alloys (MEAs). The heterogeneous FCC and BCC dual-phase FeCrNiVx MEAs (x = 0, 0.1, 0.2 and 0.3, mole fraction) were designed and prepared to elevate the mechanical properties. The addition of V induces the BCC in FeCrNi MEAs with single-phase FCC, the dual-phase morphology improves the strength and work-hardening capacity. The yield strength (σ0.2) and ultimate tensile strength (σUTS) of FeCrNiV0.3 MEA (V3) reach to 357 MPa and 855 MPa, respectively, which is elevated by 113.77 % and 94.32 % than those of V free FeCrNi MEA (V0). The strength-ductility change is attributed to the collaboration of second-phase and hetero-deformation strengthening, the dual-phase heterostructure composed of soft FCC matrix and hard BCC phase supplies the phase boundary strength, by obstructing the dislocation slip, increasing the dislocation density and promoting the strain hardening. The results supply a strategy of designing of Co-free dual-phase MEA with outstanding cost/performance advantage.